P3.171 Male spouse perpetrated psychological and sexual abuse among pregnant women in nairobi, kenya. (8th July 2017) - Mbugua, Njeri; Bukusi, Elizabeth Ann; Ngugi, Elizabeth; Mwaura, James; Nguti, David
Abstract : Introduction: The purpose of this comparative retrospective study was to evaluate the nature of male spouseperpetrated gender based violence (GBV) during pregnancy. The objective was to establish whether diagnosis of HIV infection during pregnancy mitigates or exacerbates male spouse perpetrated psychological and sexual abuse during pregnancy. Methods: Case group comprising 96 HIV infected pregnant women, and comparison group (96 uninfected), all in their third trimester of pregnancy were interviewed upon consenting. A modified Conflict Tactics Scale 2 was administered to compare the two groups in terms of psychological aggression and sexual coercion. Results: Results indicated prevalence and severity of male spouse perpetrated abuse to be higher for case group than comparison group across both psychological aggression and sexual coercion subscales. The odds of male spouse perpetrated violence was 6.64-fold higher in HIV positive pregnant women compared to HIV negative pregnant women (OR=6.64, 95% CI 1.56–28.27, p=0.010). Thus, diagnosis of pregnancy and absence of HIV infection was associated with mitigated occurrence and severity of male spouse perpetrated abuse, while diagnosis of HIV infection during pregnancy exacerbated the same. Conclusion: The investigator recommends immediate sensitisation of health and social workers attending to pregnant women on the escalative effect of HIV positive diagnosis on male-spouse perpetrated violence. Intensive couple counselling and follow up care need to be specially designed and implemented for such couple whether they are concordant positive or discordant.